Data analytics for intelligent transportation systems - Chowdhury, Mashrur A.; Apon, Amy; Dey, Kakan (Elsevier, 2017)
"Data Analytics for Intelligent Transportation Systems provides in-depth coverage of data-enabled methods for analyzing intelligent transportation systems that includes detailed coverage of the tools needed to implement these methods using big data analytics and other computing techniques. The book examines the major characteristics of connected transportation systems, along with the fundamental concepts of how to analyze the data they produce. It explores collecting, archiving, processing, and distributing the data, designing data infrastructures, data management and delivery systems, and the required hardware and software technologies. Users will learn how to design effective data visualizations, tactics on the planning process, and how to evaluate alternative data analytics for different connected transportation applications, along with key safety and environmental applications for both commercial and passenger vehicles, data privacy and security issues, and the role of social media data in traffic planning.Includes case studies in each chapter that illustrate the application of concepts coveredPresents extensive coverage of existing and forthcoming intelligent transportation systems and data analytics technologiesContains contributors from both leading academic and commercial researchersExplains how to design effective data visualizations, tactics on the planning process, and how to evaluate alternative data analytics for different connected transportation applications."--Publisher's description.